The Geological Roles Played by Microfungi in Interaction with Sulfide Minerals from Libiola Mine, Liguria, Italy. Issue 7 (9th August 2018) - Cecchi, Grazia; Ceci, Andrea; Marescotti, Pietro; Persiani, Anna Maria; Di Piazza, Simone; Ballirano, Paolo; Mariotti, Mauro Giorgio; Zotti, Mirca
ABSTRACT: The potential role played by fungi in the weathering of sulfide abandoned mines and waste rock dumps is scarcely investigated, yet. In particular microfungi may produce biofilms that work as sites of metals and minerals precipitation. This study aimed to investigate interactions, bioalteration, and biocorrosion between three microfungi ( Trichoderma harzianum group, Penicillium glandicola, P. brevicompactum ) isolated from the Libiola sulfide mine (Liguria, Italy) and pyrite-rich mineralizations occurring within the waste rock dumps. After six weeks of incubation, Environmental Scanning Electron Microscope (ESEM) analyses showed how single pyrite crystals were completely corroded and altered by all the selected species. These results represent the first step to establish that fungi play a central role in the biogeochemical cycles of extreme and contaminated sites such as sulfide mines, and that they actively contribute to the evolution of the degraded ecosystem to more harmonized scenery.